2009
DOI: 10.1016/j.joca.2009.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage damage in femoroacetabular impingement (FAI): preliminary results on comparison of standard diagnostic vs delayed gadolinium-enhanced magnetic resonance imaging of cartilage (dGEMRIC)

Abstract: We conclude that a pattern of zonal T1 variation does seem to exist that is unique for different sub-groups of FAI. The FA GRE approach to perform 3D T1 mapping has a promising role for further studies of standard MRI and dGEMRIC in the hip joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
68
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 39 publications
17
68
0
1
Order By: Relevance
“…Although we were unable to see a statistical difference in any of the individual regions between the cam and pincer impingement groups there seem to be different patterns of articular damage between the two groups. These would be in accordance with recent studies 5,8,33 which demonstrated the majority of the damage in the anterior superior region of the joint in cam hips. Additionally, the damages assessed posteriorly were only about half the damage as seen in the anterior regions, compared to the control group.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Although we were unable to see a statistical difference in any of the individual regions between the cam and pincer impingement groups there seem to be different patterns of articular damage between the two groups. These would be in accordance with recent studies 5,8,33 which demonstrated the majority of the damage in the anterior superior region of the joint in cam hips. Additionally, the damages assessed posteriorly were only about half the damage as seen in the anterior regions, compared to the control group.…”
Section: Discussionsupporting
confidence: 94%
“…Additionally, the majority of impingement patients have mixed findings of pincer and cam, which have shown to give very varied patterns of articular damage. 33 Prior to understanding these mixed patients we sought to identify cases in which a cam or pincer mechanism was clearly predominant making it difficult to obtain However, this may not be a limitation because dGEMRIC uses a method to detect the GAG content of arthritis and it has been shown to be independent of age. 33 It may be that the patients with pincer impingement, present with more advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…Beck et al [3] first described intraoperative cartilage damage in hips with cam-type FAI mainly in the anterosuperior quadrant, which is consistent with other intraoperative observations [2,14,20] and findings in computer simulation [30]. Although MRI mapping of cartilage in the hip has been shown to be feasible and capable to evaluate the biochemical status of cartilage in dysplasia [19,25,26,29] as well as cam FAI (Table 1) [4,7,9,19,[24][25][26]29], the region-of-interest (ROI) selection used in terms of size and location has varied between studies. Having said that, understanding how to best define and analyze the ROIs is still evolving and is critical to ensure reproducible and comparable results between institutions and studies.…”
Section: Introductionsupporting
confidence: 56%
“…One technique, which is sensitive to the proteoglycan content in cartilage, is delayed gadolinium-enhanced MRI of cartilage (dGEMRIC). It has been shown that dGEMRIC can serve in the evaluation of hips with dysplasia [22] or a cam deformity [4]. However, dGEMRIC requires intravenous injection of an exogenous contrast agent; other quantitative approaches for cartilage imaging that do not use contrast agents now are available, including T1q mapping.…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity for delamination assessed by MRA is only 22% [16]. Potentially more sophisticated MR techniques, such as dGEMRIC [17][18][19][20], T1rho and T2 mapping, will enable more accurate identification of cartilage damage preoperatively. A number of studies have investigated the role of dGEMRIC in FAI.…”
Section: Difficulties With Imagingmentioning
confidence: 99%